Luffa Sponge, Banana Stem and Delonix regia Seed Characterization as Potential Biosorbents for Industrial Wastewater Remediation - Ephraim G. KEFAS; Abdulfatai JIMOH; Mohammed A. EVUTI; Abubakar A. IBRAHIM; Abdulwahab GIWA; Adeola G. OLUGBENGA (FUDMA Journal of Engineering and Technology, 2025)
This paper focuses on characterizations of luffa sponge, banana stem and Delonix regia seed as potential resources for the development of biosorbents for heavy metals removal from industrial effluents. The selected materials were pretreated by washing, sun drying, and oven drying before being pulverized into powder. The powders were subjected to proximate, ultimate, chemical composition, SEM/EDX, FTIR, DTA/TGA and XRD analyses. Fixed carbon content ranges from 49.29±0.20%-52.34±0.02% for the samples. The carbon content values range from 65.27±0.01%-66.87±0.02%, and the Sulphur content ranges from 0.37±0.01%-0.81±0.001%. Cellulose content values of 41.64±0.002%, 40.86±0.001% and 45.24±0.001% were found for luffa sponge, banana stem and Delonix regia seed, respectively. SEM/EDX and FTIR confirm the presence of carbon, nitrogen, and potassium as the dominant elements, while OH-, C=C, C=O, C-H, and N-H as the surface functional groups in the precursors. The DTA/TGA shows that rapid weight loss for luffa sponge, Banana stem, and Delonix regia seed occurs between 300-420oC, 290-350oC, and 280-480oC, respectively. XRD revealed that the precursors are largely amorphous/semi-crystalline, predominantly amorphous, and a mixture of amorphous and crystalline, respectively. The above findings show that the selected precursors would be good resource for use as adsorbents/blends for the removal of heavy metals from industrial effluents.